Synthetic Strategies Toward Nitrogen-Rich Energetic Compounds Via the Reaction Characteristics of Cyanofurazan/Furoxan - Wang, Luoluo; Zhai, Lianjie; She, Weiqing; Wang, Minchang; Zhang, Junlin; Wang, Bozhou (Frontiers in Chemistry, 2022)
The structural units of amino-/cyano-substituted furazans and furoxans played significant roles in the synthesis of nitrogen-rich energetic compounds. This account focused on the synthetic strategies toward nitrogen-rich energetic compounds through the transformations based on cyanofurazan/furoxan structures, including 3-amino-4-cyanofurazan, 4-amino-3-cyano furoxan, 3,4-dicyanofurazan, and 3,4-dicyanofuroxan. The synthetic strategies toward seven kinds of nitrogen-rich energetic compounds, such as azo (azoxy)-bridged, ether-bridged, methylene-bridged, hybrid furazan/furoxan-tetrazole–based, tandem furoxan–based, hybrid furazan-isofurazan–based, hybrid furoxan-isoxazole–based and fused framework–based energetic compounds were fully reviewed, with the corresponding reaction mechanisms toward the nitrogen-rich aromatic frameworks and examples of using the frameworks to create high energetic substances highlighted and discussed. The energetic properties of typical nitrogen-rich energetic compounds had also been compared and summarized.